2020
DOI: 10.1055/s-0040-1709678
|View full text |Cite
|
Sign up to set email alerts
|

Implant Alignment and Patient Factors Affecting the Short-Term Patient-Reported Clinical Outcomes after Oxford Unicompartmental Knee Arthroplasty

Abstract: This study aims at clarifying implant alignment and other patient factors' influence on clinical outcomes, particularly on patient-reported outcomes (PRO), following Oxford unicompartmental knee arthroplasty (OUKA). A total of 142 patients after OUKA were divided into two groups according to the validated Japanese version of the knee injury and osteoarthritis outcome score (KOOS) for each subscale of pain, symptoms, and activities of daily living (ADL) at postoperative year 1 and 2: group 1 had ≥80 scores and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Previous studies have reported postoperative radiographic measurements for the alignment of the femoral component relative to the femur and the alignment of the tibial component relative to the tibia [15,[17][18][19][20][21]. We believe that bearing movement is related to changes in the relative position and angle between the femoral and tibial components.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported postoperative radiographic measurements for the alignment of the femoral component relative to the femur and the alignment of the tibial component relative to the tibia [15,[17][18][19][20][21]. We believe that bearing movement is related to changes in the relative position and angle between the femoral and tibial components.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it has also been brought up that the degenerative disorders in lateral compartments can be promoted by overcorrecting the varus deformity [22,23]. According to some reports of Oxford UKA, all the alignment of the knees via balancing the ligaments passed through the central line of the knees, which was usually similar to the contralateral part [8,[24][25]. Additionally, it was demonstrated that the operations with robotic assistance remarkably improved the alignment of the limbs following medial UKA in comparison with the conventional technique [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Femoral drilling was performed with an Oxford Microplasty device (MP: Biomet Ltd., Swindon, UK) to facilitate reproducible implant alignment [ 15 ]. After these procedures, we performed the same gap-balancing procedure between knee flexion and extension and a modified keel cutting method as that previously reported [ 16 , 17 ]. With the trial components in place, we used two candidate trial MBs with a 1-mm thickness difference with the trial components to prospectively investigate the effects of a 1-mm difference in MB thickness.…”
Section: Methodsmentioning
confidence: 99%